1987
DOI: 10.1192/bjp.151.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in Scottish Prisons

Abstract: A consecutive series of prison suicides in Scotland between 1970 and 1982 was examined. The initial phase of imprisonment was found to be the most vulnerable stage of confinement, with almost two-thirds of the deaths having taken place within the first month. A disproportionately high number were found to be on remand. A history of some form of psychiatric involvement was common, and a third of the group had received previous psychiatric inpatient treatment. In contrast to results from general population studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
6

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(63 citation statements)
references
References 7 publications
2
55
0
6
Order By: Relevance
“…4% Herrick, 1989;Michael, B., 1992;Ministry of Justice, 1996 Self-harm/Attempted Suicide 4 -40% Eyland, Corben, & Barton, 1997;Franklin, 1988;Home Office, 1984;Pattison & Kahan, 1983;Weekes & Morrison, 1992 Suicide 0.02 -0.47% Backett, 1987;Camilleri, McArthur & Webb, 1999;Flaherty, 1983;Liebling, 1992;Liebling & Krarup, 1993;McClure, 1987;Ministry of Justice, 1996;Office of Corrections Victoria, 1985;Porporino, 1992;Ramsay, Tanney, & Searle, 1987;Tatarelli,;Topp, 1979 Drug-use 1 -31% 22 -76%…”
Section: Discussionmentioning
confidence: 99%
“…4% Herrick, 1989;Michael, B., 1992;Ministry of Justice, 1996 Self-harm/Attempted Suicide 4 -40% Eyland, Corben, & Barton, 1997;Franklin, 1988;Home Office, 1984;Pattison & Kahan, 1983;Weekes & Morrison, 1992 Suicide 0.02 -0.47% Backett, 1987;Camilleri, McArthur & Webb, 1999;Flaherty, 1983;Liebling, 1992;Liebling & Krarup, 1993;McClure, 1987;Ministry of Justice, 1996;Office of Corrections Victoria, 1985;Porporino, 1992;Ramsay, Tanney, & Searle, 1987;Tatarelli,;Topp, 1979 Drug-use 1 -31% 22 -76%…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that violent or sexual offenders [11,16], repeat offenders [17,18], and those serving long sentences [19,20] are over-represented in the suicide statistics. However, a few studies contradict this pattern, finding that non-violent [21], first time offenders [20], and offenders serving shorter sentences [22] are at increased risk of suicide. Several authors found that prison suicide is associated with psychological disorders [11,18,23], alcohol and drug misuse [10,18], a history of selfharm [10,11], isolation [11,24], and prison overcrowding [25].…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, other reports showed that natural diseases were a leading cause of death [9]. Some risk factors for inmate suicides identified in earlier studies were the number of days following incarceration [10,11], overcrowding [12], isolation [13], long sentences after high violent offences [14], psychiatric disorders, alcohol and drug abuse [15,16], and depression [16]. Deaths other than those due to suicide could be as a result of physical disease processes, homicide, accidents and misadventures.…”
Section: Introductionmentioning
confidence: 44%